Evaluation of Inclusion Education at SMP Negeri 21 North Jakarta - Mardiawati*, Nuramaliah; Muljono, Hery; Syarif, Moh.Suryadi (Universitas Syiah Kuala, 2023)
This study aims to find information about the design, installation, processes, products, and benefits of inclusive education at SMP Negeri 21. The evaluation model used is the Discrepancy Evaluation Model which includes five stages: (1) design, (2) installation, (3) process, (4) product, and (5) benefit. The method used is descriptive qualitative which includes data collection using observation, interviews, and documentation. The results of the study can be concluded based on the evaluation of the gaps in stage (1) of the design evaluation, namely that there are no gaps in implementing inclusive education according to the goals of inclusive education. In stage (2) of the installation evaluation, there are gaps in five aspects, namely curriculum, financing, teaching staff, and support infrastructure or cooperation from the school community. In stage (3) process evaluation there are gaps in three aspects, namely learning activities, expert teaching staff, and infrastructure. In stage (4) product evaluation, there are gaps in aspects of academic and non-academic assessments. Lastly, in stage (5) a comparative evaluation of the benefits of inclusive education for schools, that there are differences in the learning-teaching activities for inclusive students and the benefits for inclusive students themselves, there is a behavior change that is better than before.